Ischaemia alters the effects of cardiomyocyte‐derived extracellular vesicles on macrophage activation. Issue 2 (4th December 2018) - Almeida Paiva, Rafael; Martins‐Marques, Tania; Jesus, Katia; Ribeiro‐Rodrigues, Teresa; Zuzarte, Monica; Silva, Ana; Reis, Liliana; da Silva, Maria; Pereira, Paulo; Vader, Pieter; Petrus Gerardus Sluijter, Joost; Gonçalves, Lino; et al.
Abstract: Myocardial ischaemia is associated with an exacerbated inflammatory response, as well as with a deregulation of intercellular communication systems. Macrophages have been implicated in the maintenance of heart homeostasis and in the progression and resolution of the ischaemic injury. Nevertheless, the mechanisms underlying the crosstalk between cardiomyocytes and macrophages remain largely underexplored. Extracellular vesicles (EVs) have emerged as key players of cell‐cell communication in cardiac health and disease. Hence, the main objective of this study was to characterize the impact of cardiomyocyte‐derived EVs upon macrophage activation. Results obtained demonstrate that EVs released by H9c2 cells induced a pro‐inflammatory profile in macrophages, via p38MAPK activation and increased expression of iNOS, IL‐1β and IL‐6, being these effects less pronounced with ischaemic EVs. EVs derived from neonatal cardiomyocytes, maintained either in control or ischaemia, induced a similar pattern of p38MAPK activation, expression of iNOS, IL‐1β, IL‐6, IL‐10 and TNFα. Importantly, adhesion of macrophages to fibronectin was enhanced by EVs released by cardiomyocytes under ischaemia, whereas phagocytic capacity and adhesion to cardiomyocytes were higher in macrophages incubated with control EVs. Additionally, serum‐circulating EVs isolated from human controls or acute myocardial infarction patients induce macrophage activation. According to our model, in basal conditions, cardiomyocyte‐derived EVs maintain a macrophage profile that ensure heart homeostasis, whereas during ischaemia, this crosstalk is affected, likely impacting healing and post‐infarction remodelling.